TikTok fined €530m by Irish regulator for failing to guarantee China would not access user data - Milmo, Dan (The Guardian, 2025)
Ireland’s Data Protection Commission found video app breached GDPR and had submitted ‘erroneous information’ to inquiry.
Ireland
Keywords: Business; China; Data protection; European Union; Ireland; Privacy; Social media; Surveillance; Technology; TikTok; World news